Similarities and differences between notions of ‘public’ in the Sinic and liberal Anglo-American traditions, and the implications for higher education - Yang, L (2020)
This thesis conceptually explores, compares, and searches for potential complementarities, hybridisations, and synergies of ideas concerning the public (good) of higher education in the Sinic and liberal Anglo-American traditions. A common trope, particularly in the liberal Anglo-American tradition, is the notion that higher education produces public goods. However, there is a lack of clarity about what this means; and the dominant economic or political explanations of higher education’s public goods often fail outside Anglo-American societies, especially in China where society follows a tradition of having a comprehensive state. Such a problem not only limits the understanding of the public (good) of higher education, but results in difficulties in cross-cultural understanding and cooperation in higher education. In order to establish a broader understanding of the public (good) of higher education, the thesis employs a two-step trans-positional comparative methodology, built on Amartya Sen’s trans-positional analysis. Following the account of the methodology, the study starts with an exploration of broad cultural and philosophical ideas underlying the public (good) of higher education in the two traditions. The exploration further reveals the social imaginaries of the two traditions, referring to the understandings of four primary spheres of social action – the spheres of individual, society, the state, and the world – and the relationship between the four spheres. It then compares the social imaginaries between the two traditions and examines how higher education interacts with the four spheres of social action. Five key themes of the public (good) of higher education are identified in this process, demonstrating the intersection between higher education and the individual, society, the state, and the world.